Viable baby from a couvelaire uterus - R.C. Karki, Laxmi; Das, Chitra Ranjan (Journal of Patan Academy of Health Sciences, 2015)
A 20-year-old primi gravida of 32 weeks pregnancy by date was admitted in the labor room with diagnosis of preterm labor with preeclampsia. Ultrasonography revealed 36 weeks pregnancy with normal liquor volume and fundal placenta. Lower segment caesarean section was done for cephalopelvic disproportion with preeclampsia. A female baby was delivered weighing 2.4 kg, with Apgar score of 6/10, 8/10. The placenta was delivered by control cord traction. On the fundus 25% of placenta was already separated and 500 ml of old retro placental clots were found. It was abruption placentae (concealed type), the uterus was bluish/purplish color, which was diffuse on fundal area and effusions of blood were also seen beneath the tubal serosa. After delivery of the baby uterus was well contracted 20 weeks size, bilateral ovaries were normal.Journal of Patan Academy of Health Sciences. 2014 Dec;1(2):49-51